Recentring the Political in Education for Sustainable Development: Participatory Photovoice Research as Prefigurative Politics Towards Social-ecological Transformation - Fabian Pettig; Daniela Lippe (Australian Journal of Environmental Education)
Based on the critique of education for sustainable development (ESD) as a socio-political control element of ecological modernisation, we discuss the prefigurative potential of participatory photovoice research in schools in light of social-ecological transformation. We argue that engaging students in prefigurative practices of change in which (sustainable) counter-futures are explored in the (unsustainable) present can help to re-politicise ESD, and we view photovoice as a way to guide this transformative process. Drawing on examples from a participatory research project on the transformation of local food systems in Graz, Austria, we critically explored photovoice as a method of transformative education that creates power-critical spaces of possible futures in which (un)sustainable hegemony and collectively internalised patterns of thought and action can be questioned to envision and negotiate liveable futures for all.